Emergence of Popular Historical Culture in Russia: National History Illustrated in the Mid-Nineteenth-Century Publications - Chernysheva, Maria A. (Actual Problems of Theory and History of Art, 2022)
I look at how Russian history was illustrated in publications of the 1830–1870s, with an emphasis on the special role that prints played among pictorial and verbal representations of Russian history. The greatest attention is paid to “Picturesque Karamzin, or Russian History in Pictures” and “History of Russia in Pictures”. The transformation of historical consciousness from the pre-reform to the post-reform era is traced through a comparative analysis of the visual content of these richly illustrated publications. I construct a typology of new historical themes and meanings appearing in “History of Russia in Pictures”, which were unacceptable in the public visual space in the Nicholas’ time. The key area of disagreement between “Picturesque Karamzin” and “History of Russia in Pictures” is the depiction of Ivan the Terrible. I demonstrate that while performing educational and popularizing functions, historical illustration acted as an experimental field for visualizing the new historical ideas that were previously formed in science and fiction. Often, new historical themes first migrated from historiography and literature into prints and only after that got transferred to painting. The dependence of historical paintings on the available patterns was greater in the epoch of Nicholas I than in the time of Alexander II. And since the 1860s, the paintings that were dedicated to national history and had no thematic precedents in the visual arts began to appear in Russia primarily because the artists themselves started to study historical literature in direct, individual, and independent ways. And this became one of the key symptoms of the historization of artistic consciousness.